2012
DOI: 10.1148/radiol.12102492
|View full text |Cite
|
Sign up to set email alerts
|

Malformations of Cortical Development: Diagnostic Accuracy of Fetal MR Imaging

Abstract: Purpose:To determine the diagnostic accuracy of fetal magnetic resonance (MR) imaging for malformations of cortical development by using postnatal MR imaging as reference standard. Materials and Methods:Eighty-one patients who had undergone fetal and postnatal MR imaging of the brain were identified in this institutional review board-approved, HIPAA-compliant study.Images were retrospectively reviewed in consensus by two pediatric neuroradiologists who were blinded to clinical information. Sensitivity and spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
58
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 18 publications
7
58
0
3
Order By: Relevance
“…3,14,15,20,21 However, very few describe the diagnostic accuracy. 17,22 The largest published series of 15 patients reported that fetal MR imaging was up to 73% sensitive and 100% specific for diagnosing SEH. 17 Our study examined a much larger cohort of patients, increasing the validity of our findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…3,14,15,20,21 However, very few describe the diagnostic accuracy. 17,22 The largest published series of 15 patients reported that fetal MR imaging was up to 73% sensitive and 100% specific for diagnosing SEH. 17 Our study examined a much larger cohort of patients, increasing the validity of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…17,22 The largest published series of 15 patients reported that fetal MR imaging was up to 73% sensitive and 100% specific for diagnosing SEH. 17 Our study examined a much larger cohort of patients, increasing the validity of our findings. However, we focused on a specific population of patients, looking only at fetuses with prenatally diagnosed spinal dysraphisms; this type of search decreased the generalizability of our findings.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The largest published series are those of Oh et al (6 cases) 3 and Denis et al (3 cases). 17 Both of these studies were limited to subjects with open-lip schizencephaly (unilateral or bilateral), and the pregnancy was terminated in all 3 subjects in the study of Denis et al Recent work by Glenn et al 25 on a relatively large series of fetal MR imaging in subjects with malformations of cortical development included 3 subjects with schizencephaly. In their study, fetal MR imaging had 100% sensitivity and specificity for the prenatal diagnosis of schizencephaly in their 3 patients (both open and closed).…”
Section: Discussionmentioning
confidence: 99%